328 An Integrated Approach to Fear of Falling. (16th September 2019) - Murphy, Eleanor; McLoughlin, Petra; O'Sullivan, Fiona; Connellan, Ciara
Abstract: Background: Fear of falling (FOF) is a known risk factor for falls and subsequent activity restriction which has implications for quality of life and frailty level in older persons. 1 The Integrated Care Team for Older Persons in Sligo provides home-based rehabilitation for the acutely frail older adult. We noted that fear of falling was a commonly identified problem in our referral group following comprehensive geriatric assessment (CGA). Our study aims to characterise interventions required. Methods: Descriptive study from CGA of acutely frail older adults with a FOF in all referrals to ICTOP from June to December 2018. Results: Of the 52 patients studied, 67% reported a FOF with a higher incidence in females (81% vs 45%). Increasing age was associated with a greater likelihood of FOF with 0% reported at 70-74years (n=4) and 86% at 90-95 years (n=7). There was a 1.6 times increased risk of FOF associated with cerebral vascular disease and 1.26 with mental health issues. The median Rockwood Clinical Frailty score was 6 with a median TUG of 28 seconds. Of those with a FOF, 100% received falls education, a home exercise program and advice on acquiring a pendant alarm. A mobility aid was provided in 63% and additional functional aids in 71%. Major housing adaption advice was given in 50% and additional equipment signposting and purchasing advice in 66%. Transport advice was provided in 49% of cases and onward referrals to ophthalmology and orthotics were provided in 9% and 11% respectively. There were only 2 readmissions with a fall within 30 days. Conclusion: A significant cohort of ICTOP referrals report a fear of falling. Specific physiotherapy and occupational therapy interventions aim to reduce the impact of this and our low rate of readmissions due to falls indicates the success of this program.